HOT ABSORPTION OF HEAT ABSORPTION IN MAIN ENGINE LUBRICATING OIL COOLER - Rachman, Abdul Nasir (Indonesian Journal Of Maritim Review, 2023)
Ships are a means of sea transportation that use diesel engines as the main driving force. This is because diesel engines are easier to maintain and faster to operate. Considering this, diesel engines need special attention so that they are always ready to use and work well to support activities on board. The aim of this research is to determine the causal factors and what efforts must be made to overcome the obstruction of heat absorption in the lubricating oil of the main engine on the MT.AnnaBella ship. The research results show that the cause of the lack of oil cooler lubrication absorption on the main engine at MT.AnnaBella is due to lack of maintenance on the lubrication system components, namely dirty Lo cooler sea water pipes, dirty sea chase filters, resulting in decreased sea water pump suction, and dirty impellers. pump the sea water pump so that the sea water pump pressure decreases. Efforts to overcome the obstruction of heat absorption in the lubricating oil of the main engine on the MT AnnaBella include paying attention to the cleanliness of the sea water pipes in the lo cooler. By spraying compressed air and using rattan, always pay attention to the cleanliness of the sea water filter and regularly check the sea water pump impeller for dirt.